2007
DOI: 10.1097/gim.0b013e3180654ccd
|View full text |Cite
|
Sign up to set email alerts
|

The NAD(P)H:quinone oxidoreductase I C609T polymorphism modifies the risk of Barrett esophagus and esophageal adenocarcinoma

Abstract: Purpose: The role of genetic susceptibility to esophageal adenocarcinoma and its precursor lesion Barrett esophagus has not been fully elucidated. This study investigated the effect of polymorphisms in the manganese superoxide dismutase (MnSOD) and NAD(P)H:quinone oxidoreductase 1 (NQO1) genes in modulating the risk of developing Barrett esophagus or esophageal adenocarcinoma. Methods: A total of 584 patients (146 esophagitis, 200 Barrett esophagus, 144 esophageal adenocarcinoma, and 94 controls) were genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…There are conflicting reports on the potential association between the Ala allele and gastric cancer (Martin et al, 2005;Yi et al, 2010). Other forms of cancers studied include colorectal, oesophageal, pancreatic, ovarian and skin, with all reporting no association with SOD2 genotypes (di Martino et al, 2007;Funke et al, 2009;Han et al, 2007;Johnatty et al, 2007;Li et al, 2002;Martin et al, 2005;Murphy et al, 2007;Sun et al, 2009). …”
Section: Other Cancersmentioning
confidence: 97%
See 1 more Smart Citation
“…There are conflicting reports on the potential association between the Ala allele and gastric cancer (Martin et al, 2005;Yi et al, 2010). Other forms of cancers studied include colorectal, oesophageal, pancreatic, ovarian and skin, with all reporting no association with SOD2 genotypes (di Martino et al, 2007;Funke et al, 2009;Han et al, 2007;Johnatty et al, 2007;Li et al, 2002;Martin et al, 2005;Murphy et al, 2007;Sun et al, 2009). …”
Section: Other Cancersmentioning
confidence: 97%
“…Twenty-one studies have investigated the relationship between the SOD2 Ala16Val SNP and other cancers (di Martino et al, 2007;Han et al, 2007;Hirvonen et al, 2002;Ho et al, 2006;Hung et al, 2004;Ichimura et al, 2004;Johnatty et al, 2007;Koistinen et al, 2006;Landi et al, 2007;Li et al, 2002;Lightfoot et al, 2006;Lin et al, 2003;Liu et al, 2004;Mak et al, 2007;Martin et al, 2005;Murphy et al, 2007;Sun et al, 2009;Wang et al, 2004Wang et al, , 2006Young et al, 2006;Zejnilovic et al, 2009). Wang et al (2004) found that individuals with the Val allele had an increased risk of lung cancer if there was low or no asbestos exposure compared to high exposure (OR 2.14, 95% CI 1.52-3.01), although the small number in the high asbestos exposure group limited the validity of the findings.…”
Section: Other Cancersmentioning
confidence: 99%
“…Briefly, of the 22 studies (Wang et al, 2001;Woodson et al, 2001;Lin et al, 2003;Liu et al, 2004;Wang et al, 2004;Li et al, 2005;Taufer et al, 2005;Ho et al, 2006;Choi et al, 2007;di Martino et al, 2007;Ergen et al, 2007;Kang et al, 2007;Arsova-Sarafinovska et al, 2008;Iguchi et al, 2008;Mikhak et al, 2008;Bica et al, 2009;Cheng et al, 2009;Iguchi et al, 2009;Sun et al, 2009;Zejnilovic etal., 2009), the sample size ranged between 100 and 3,030, and there were twelve studies on prostate cancer, four studies on esophageal cancer, and six studies on lung cancer. All studies, except for five of them (Taufer et al, 2005;Bica et al, 2009;Sun et al, 2009;Zejnilovic et al, 2009), indicated that the distribution of genotypes in the controls was consistent with HardyWeinberg equilibrium, while only one study conducted by Lin et al (2003) contained no data for Hardy-Weinberg equilibrium.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Recent data have suggested an association between polymorphisms of two detoxifying enzymes [NAD(P)H:quinone oxidoreductase and glutathione S-transferase P1] and the risk of developing Barrett's and OAC (Casson et al, 2006;di Martino et al, 2007;Redon et al, 2006). Another candidate genetic marker of Barrett's susceptibility is cyclin D1, whose function as part of the cell cycle machinery is to allow progression to S-phase.…”
Section: Genetic Predisposition To Barrett's Oesophagusmentioning
confidence: 99%